Global Governance
XIV, 318 p.
Keywords: This book provides the first comprehensive analysis of global governance from a gendered perspective. It not only furthers the emerging feminist theorizing on global governance, but also provides a theoretically informed and empirically based analysis of both institutions and transformative practices.